Exploring the Effect of Anti-immigration Rhetoric on Emergency Department Use by Undocumented Adults. - Bao, Juan; Sun, Leon; Nguyen-Hoang, Phuong; Momany, Elizabeth T. (Journal of Immigrant & Minority Health, 2024)
An unwelcoming policy climate can create barriers to health care access and produce a 'Chilling Effect' among immigrant communities. For undocumented immigrants, barriers may be unique and have a greater impact. We used administrative emergency department (ED) data from 2015 to 2019 for a Midwestern state provided under a data use agreement with the state hospital association. General linear modelling was used to estimate the impact of anti-immigrant rhetoric on ED visit intensity among non-elderly adults who were likely Hispanic/Latino with undocumented status. Compared to 2015, the average ED visit intensity among adults who were likely Hispanic/Latino with undocumented status was significantly higher during 2016–2019 when anti-immigrant rhetoric was heightened. The magnitude of this change increased over time (0.013, 0.014, 0.021, and 0.020, respectively). Additionally, this change over time was not observed in the comparison groups. Our findings suggest that anti-immigrant rhetoric may alter health care utilization for adults who are likely Hispanic/Latino with undocumented status. Limitations to our findings include the use of only those likely to be Hispanic/Latino, data from only one Midwestern state and the loss of data due to non-classification using the NYU ED algorithm. Further research should focus on validating these findings and investigating these identification methods and anti-immigrant rhetoric effects among other undocumented groups including children and adults of different race or ethnicity such as black, both those that identify as Hispanic/Latino and those that do not. Developing strategies to improve health care access for undocumented Hispanic/Latino adults also warrants future research.